A Comparison of neoadjuvant chemotherapy and concurrent chemoradiotherapy for for FIGO 2018 stage IB3/IIA2 Cervical squamous cell carcinoma: Long-term efficacy and safety in a resource-limited setting. - Renxian Xie; Keyan Xie; Xiaoluan Lin; Yanchen Ji; Jianzhou Chen; Chuangzhen Chen (PLoS ONE)
Purpose The purpose of this research was to evaluate the effectiveness and safety of neoadjuvant chemotherapy plus radical surgery (NCRS) and concurrent chemoradiotherapy (CCRT) based on three-dimensional conformal radiation therapy (3DCRT) for FIGO 2018 stage IB3/IIA2 patients with cervical squamous cell carcinoma in a resource-limited setting. Methods The clinical outcomes and incidence of complications in 137 patients who underwent NCRS with those of 163 patients who CCRT based on 3DCRT were compared. Propensity score matching (PSM) analysis was used to match the two groups to enable further statistical comparisons. Survival analysis was performed utilizing Cox proportional hazards regression analyses, Kaplan-Meier curves, and log-rank tests. Furthermore, the incidence of complications between the two groups was also compared using chi-squared tests. Results PSM analysis identified 103 matched pairs of patients. The NCRS and CCRT groups exhibited 5-year overall survival (OS) rates of 85.4% and 91.2%, respectively (p=0.19). Additionally, the NCRS and CCRT groups exhibited 5-year disease-free survival (DFS) rates of 76.7% and 89.3% (p=0.02), and the recurrence rates were 20.4% and 9.7% (p=0.03), respectively. However, the CCRT group exhibited a higher incidence of early any-grade complications (79.6% vs 35.9%, p<0.001) and early grade 3 complications (15.5% vs 2.9%, p=0.002) compared to the NCRS group. In terms of overall late complications, there was no significant difference in the incidence between the two groups. Multivariate analysis revealed that stage IIA2 emerged as an independent risk factor for OS (aHR 8.89; p=0.033). Moreover, histologic grade 2-3 (aHR 5.3; p=0.022), stage IIA2 (aHR 2.95; p=0.043), NCRS treatment (aHR 2.41; p=0.012) were identified as independent risk factors for DFS. Conclusion In resource-limited settings, for patients with FIGO 2018 stage IB3/IIA2 cervical squamous cell carcinoma, 3DCRT-based CCRT offers superior disease-free survival and reduced recurrence rates compared to NCRS, despite increased early complication rates.